Knowledge, attitude and anxiety of medical students about the current COVID-19 outbreak in Turkey - Burkay Yakar; Türkkan Öztürk Kaygusuz; Edibe Pirinçci; Erhan Önalan; Yusuf Haydar Ertekin (SERNEV, 2020)
Introduction: The aim of this study was to assess the knowledge, attitude, and behavior of medical students about the COVID-19 and the effect of the outbreak on the students' anxiety levels.Methods: The cross-sectional study was carried out between 07-14 April, with the online questionnaire forms applied to the medical students. A questionnaire forms were sent to one of every two students in the faculty using the systematic sampling method. A total of 530 volunteers were included in the study. The data was collected through a self-administered questionnaire of the socio-demographic characteristics, opinions about the epidemic, knowledge, and attitude of medical students regarding COVID-19. Anxiety levels of the participants were measured with the State-Trait anxiety inventory.Results: A total of 530 medical students had a mean score of knowledge and attitude of 7.83±1.27 and 45.18±5.12, respectively. Participants demonstrated good knowledge and a positive attitude towards COVID-19. Clinical period students had a higher level of knowledge (p lt;0.001) and positive attitude (p=0.025) compared to preclinical students. While the knowledge score was higher in men (p = 0.033), the attitude score was higher in women (p lt;0.001). There was a negative correlation between attitude scores and state (p=0.003) and trait anxiety scores (p lt;0.001).Conclusion: Medical students had sufficient knowledge and attitude towards COVID-19. Anxiety caused by the outbreak may have negative effects on the positive attitudes of the participants.